2008
DOI: 10.1677/joe-08-0036
|View full text |Cite
|
Sign up to set email alerts
|

Biphasic response of endothelial progenitor cell proliferation induced by high glucose and its relationship with reactive oxygen species

Abstract: In this study, the effect of high glucose (HG) on endothelial progenitor cell (EPC) proliferation and its relationship with cyclins and reactive oxygen species (ROS) were investigated. Mouse EPCs were isolated from bone marrow using a magnetic activated cell-sorting system and cultured in the presence or absence of HG (30 mmol/l). We found that in the early stage of incubation (3 days), HG promoted cell proliferation, and increased the expressions of cdk2 and cyclin E, while in the late stage of culture (7 day… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
10
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 18 publications
2
10
0
Order By: Relevance
“…25) Inhibition of oxidative stress has reversed diabetic EPC dysfunction, suggesting that increased ROS plays key roles in diabetic vascular impairment. 5,25,26) The increased level of ROS in EPCs was also detected under HG condition, 27) and here we further demonstrated the enhanced mitochondrial ROS and disruption of mitochondrial membrane potential in HG-exposed EPCs, suggesting its role in HG-induced autophagy in EPCs. Mitochondrial ROS generation and subsequent mitochondrial oxidative damage may modulate mitophagy, a form of micro-autophagy, potentially contributing to autophagic cell death.…”
Section: Discussionsupporting
confidence: 78%
“…25) Inhibition of oxidative stress has reversed diabetic EPC dysfunction, suggesting that increased ROS plays key roles in diabetic vascular impairment. 5,25,26) The increased level of ROS in EPCs was also detected under HG condition, 27) and here we further demonstrated the enhanced mitochondrial ROS and disruption of mitochondrial membrane potential in HG-exposed EPCs, suggesting its role in HG-induced autophagy in EPCs. Mitochondrial ROS generation and subsequent mitochondrial oxidative damage may modulate mitophagy, a form of micro-autophagy, potentially contributing to autophagic cell death.…”
Section: Discussionsupporting
confidence: 78%
“…It has been known that low baseline levels of ROS produced in response to tissue ischemia serve as intracellular signaling molecules to prevent tissue injury and promote angiogenesis [24,25], but excess amounts of ROS impair EPC function and induce vascular injury [26]. Previous studies also showed that HG and AGEs induced ROS production and overexpressed oxidant stress in EPCs and other cell types [12,13,14,27,28]. Inflammatory markers such as TNF-α and CRP also caused vascular dysfunction [29] and the reduction and dysfunction of EPCs [30,31,32], and HG and AGEs induced IL-6 and TNF-α expression [33,34].…”
Section: Discussionmentioning
confidence: 99%
“…This study aimed to investigate how HG and AGEs regulate the expression of miR-126. Previous studies have shown that HG and AGEs adversely affect EPC function, which may be related to reactive oxygen species (ROS) [12,13,14], so we also aimed to investigate whether miR-126 mediates the effects of HG and AGEs on EPCs in relation to ROS as well as inflammatory markers. The findings will help the understanding of the mechanism of EPC dysfunction and vascular disease in DM.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, ROS generated in response to hyperglycemia (Zhang et al, 2008b) accelerated the senescence of stem and progenitor cells and inhibited angiogenesis (Dernbach et al, 2004). Tempol largely prevented the inhibition of proliferation of progenitor cells by high glucose concentrations (Zhang et al, 2008b).…”
Section: Major Organ Effects Of Tempolmentioning
confidence: 99%
“…Tempol largely prevented the inhibition of proliferation of progenitor cells by high glucose concentrations (Zhang et al, 2008b). Other studies have documented a pro-angiogenic action of tempol that may relate to a decrease in O 2 .- and thereby to increased NO bioactivity.…”
Section: Major Organ Effects Of Tempolmentioning
confidence: 99%